New Zealand : 2018 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2018)
New Zealand's economy has enjoyed a solid expansion since 2011. With a persistent net migration wave, potential output has moved closely in line with actual output, and economic slack has decreased slowly. Macroeconomic imbalances overall have narrowed, although macro-financial vulnerabilities have risen with rapid house price increases. The new coalition government seeks to make growth more inclusive.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet